Endophthalmitis after tooth extraction in a patient with previous perforating eye injury - Ogurel, Tevfik (Pan Afr Med J, 2015)
The aim of this stuty is to describe a case of endophthalmitis after tooth extraction in a patient with previous perforating eye injury. 50 years old male patient attempted to our clinic with complaints of sudden severe pain, reduced vision, light sensitivity and redness in the right eye. The patient stated that severe pain in his eye began approximately 12 hours following tooth extraction. The patient's ocular examination revealed a visual acuity of hand motion in the right eye. Anterior segment examination of the right eye showed intense conjunctival hyperemia, chemosis, a fine keraticprespitat and corneal edema. Dental procedures of the patients who had recently underwent ocular surgery or trauma should be done in a more controlled manner under anti -infective therapy or should be postponed in elective procedures.